An Investigation of Proxemic Behavior among Acehnese in Public Places - Rusma Setiyana; Nyak Mutia Ismail; Endah Annisa Rahma; Faizatul Husna (Soegijapranata Catholic University, 2018)
It is assumed that Acehnese do not make use of personal space during interactions. This study aims to investigate the proximity levels used by Acehnese people when communicating with other people. The observation approach was used to collect data with people who were in natural interaction in public places as the participant. The data were pictured and kept anonymous in regards of ethical codes maintained in research. The results show that there are three conditions obtained from this study. First, mostly, Acehnese people use intimate level of proximity, which is less than 0.46 meter eventhough when they are interacting with strangers. However, this condition only applies if the interactions taking place is male-male interactions or female-female interactions. Second, in a condition where the stranger interaction is male-female, the proximity employed by the people is in the level of personal—which is 1.2 meter. Lastly, men maintained farther distance compared to women. In conclusion, the farthest proximity level that Acehnese applied was social level (1.2 m to 3.7 m); yet, the main influencing factor is genders.